Los recursos digitales para el aprendizaje de la matemática, noveno grado, del colegio “27 de Febrero”, Loja 2022 - 2023 - Granda Granda, Widinson Giovanny (2023)
This research work is about digital resources in the learning of mathematics of students of ninth grade at "27 de Febrero" High School in the city of Loja during the 2022 – 2023 school year, it was worked with the following general objective: Determine the influence of digital resources in the learning of the subject of mathematics in the students of ninth grade "A" at "27 de Febrero" High School. Likewise, we worked with the scientific, analytical, synthetic, hypothetical-deductive, statistical, bibliographic methods, and with the techniques of a survey directed to the students and an interview applied to the teacher, in the same way with a population of 24 human beings, distributed among 23 students and 1 teacher, with the purpose of elucidating the investigated problem, it was determined that thanks to the application of digital resources it was facilitated to the students to know diverse digital tools which help them to solve mathematical problems and understanding of the given contents. We concluded that digital resources are an innovative alternative which allow students to develop their creativity and imagination so that learning is more meaningful in the subject of mathematics. Key words: digital resources, learning, human beings, innovation, creativity, imagination.